Control problems far nonlinear variational evolution inequalities - Su, Jin Cheon (Trường Đại học Đà Lạt, 2012)
In this paper, we deal with the approximate controllability for the nonlinear functional differential equation governed by the variational inequality in Hilbert spaces and present a general theorems under which previous results easily follow. The common research direction is to find conditions on the nonlinear term such that controllability is preserved under perturbation.